ANALYSIS OF COMMUNICATION SKILLS OF JUNIOR HIGH SCHOOL STUDENTS ON CLASSIFICATION OF LIVING THINGS TOPIC - Alfi Rodhiyah Zulfa; Zuhriyatur Rosyidah (INSECTA: Integrative Science Education and Teaching Activity Journal, 2020)
This study aims to determine the level of communication skills of students at SMPN 2 Ponorogo. This research was conducted in October 2019 at SMPN 2 Ponorogo. The method is a qualitative study with a sample of VII H class students in SMPN 2 Ponorogo consisting of 31 students obtained from random sampling. The design of this study used a survey design or the provision of written tests to students and interviews. The data collection technique is carried out by providing a description test to measure students' communication skills and non-structured interviews to students and teachers. Analysis of the data in this study was using qualitative descriptive and quantitative descriptive techniques. The results showed that the level of communication skills of VII grade students of SMPN 2 Ponorogo was still relatively low. The average value obtained is generally 56.9. So, the communication skills of students at SMPN 2 Ponorogo still need to be improved. Some efforts to train students in improving their communication skills are by conducting teaching and learning processes with learning models that are oriented towards students, conducting learning with active discussion, accustoming students to read, providing interesting learning facilities and media, and conducting learning activities with experiment or student worksheets.